A study of rice stem borer and rice bug population in two selected area of paddy field / Nik Syafiqah Nik Hashim - Nik Hashim, Nik Syafiqah (Faculty of Plantation and Agrotechnology, 2018)
Rice (Oryza sativa) are the major sources of food to all the people. Malaysia is the major rice importer while Thailand and Vietnam are the major suppliers of the rice. The main objective of this study is to identify the population of rice bug (Leptocorisa acuta) and stem borer (Scirpophaga incertulas) at two different area of paddy field using yellow pan traps. The research was observed at Kampung Parit Putat and Kampung Parit Penghulu around six weeks by using yellow pan trap. The data were collected eight times with nine replications. The result was analyse by using SPSS software. The factor of road and colour of trap may cause the change of population of stem borer and rice bug. The population of both insect depend on the place of paddy field that are chosen.